2017
DOI: 10.1007/s10930-017-9737-7
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Metallothionein in Rat Liver by Zinc Exposure: A Dose and Time Dependent Study

Abstract: Metallothioneins (MTs) are low molecular weight ubiquitous metalloproteins with high cysteine (thiol) content. The intracellular concentration of zinc (Zn) is tightly regulated and MT plays a crucial role in it. The present study investigates the relationship between the Zn status (as a function of Zn concentration and time) in the rat liver and the occurrence of hepatic MT. For dose dependent study, four experimental groups, one control and three receiving different levels of metal supplementation, were chose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…In vivo, previous researches have indicated that dietary supplementation with Zn could increase MT mRNA expression in the liver of broilers ( Azad et al., 2017 ; Zhang et al., 2017 ; Zhu et al., 2017b ). In vitro, it has been reported that the induction of MT conferred protection against ROS in liver ( Garla et al., 2017 ), kidney ( Sharma et al., 2002 ) and islet ( Li et al., 2004 ) cells. In the present study, either iZn or oZn increased MT mRNA expression in heat-stressed hepatocytes, suggesting that Zn-treated hepatocytes might be better prepared to deal with oxidative stress induced by heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, previous researches have indicated that dietary supplementation with Zn could increase MT mRNA expression in the liver of broilers ( Azad et al., 2017 ; Zhang et al., 2017 ; Zhu et al., 2017b ). In vitro, it has been reported that the induction of MT conferred protection against ROS in liver ( Garla et al., 2017 ), kidney ( Sharma et al., 2002 ) and islet ( Li et al., 2004 ) cells. In the present study, either iZn or oZn increased MT mRNA expression in heat-stressed hepatocytes, suggesting that Zn-treated hepatocytes might be better prepared to deal with oxidative stress induced by heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…Zn injection has induced metallothionein biosynthesis in the pancreas 17 and kidneys 19 of pigs and the livers of rats. 5 We did not investigate the expression of metallothionein in our case; however, high levels of induced metallothionein might have bound Zn in the tissues and blocked staining of the Zn.…”
mentioning
confidence: 85%
“…The oral administration of zinc leads to the expression of metallothioneins in the enterocytes, which bind the copper taken up with food and prevent its transfer into the bloodstream. During the process of natural turnover of enterocytes, bound copper is excreted with the feces [ [242] , [243] , [244] , [245] , [246] , [247] ]. In addition, zinc salts also induce the expression of metallothioneins in the liver and thus strengthen the endogenous defense [ 248 ].…”
Section: Genetically Induced Chronic Copper Overload – Wilson Diseasementioning
confidence: 99%